Novel LiV(PO4)0.9F1.3 with ultrahigh rate capability and prolonged cycle life. Issue 75 (21st August 2019) - Zhang, Meichen; Zhou, Yongmao; Ding, Xiaobo; Yan, Guochun; Wang, Zhixing; Wang, Jiexi
Abstract : Novel triclinic LiV(PO4 )0.9 F1.3, characterized through its crystal lattice expansion, ultrafine primary particle size and uniform carbon coating, was fabricated and exhibited excellent electrochemical performance. Abstract : Novel triclinic LiV(PO4 )0.9 F1.3, characterized through its crystal lattice expansion, ultrafine primary particle size and uniform carbon coating, was designed and fabricated through regulating the PO4 /F ratio. It exhibited excellent electrochemical performance, maintaining 105 mA h g −1 at 50C and 92.9% capacity retention after 500 cycles at 10C due to its superior structural stability, greater charge transfer properties, enhanced electronic conductivity and fast Li + diffusion kinetics.